Technology trends : third International Conference, CITT 2017, Babahoyo, Ecuador, November 8-10, 2017, Proceedings /: third International Conference, CITT 2017, Babahoyo, Ecuador, November 8-10, 2017, Proceedings. (2018) - Unknown
No abstract available